Analysis of Figurative Language and Meaning in the Four Album by One Direction - Yayang Sasa Anissa; I Putu Andri Permana (Austronesian: Journal of Language Science & Literature, 2023)
This study analyzes the figurative meaning of One Direction’s song lyrics, especially in the album “Four.” In this study, qualitative methods were used to carry out a well-organized description of the identified problems. The theme contained in the album “Four” is conveyed using the theory of McCarthy (1999). Theory from Knickerbocker & Reninger (1963) used to find the kinds of figurative language in song lyrics and to analyze the meaning of the figurative language used theory from Leech (1985). A singer, in expressing ideas or conveying feelings that are felt, is poured in song lyrics so the message of the implied meaning can be conveyed to the audience. In this study, seven figurative languages can be found, 3 of which are the most dominant or often used in hyperbole, personification, and simile in song lyrics. In this study, the meaning of each lyric contained in the song can be explained by the meaning contained in the album, which is about a man who is in love with a woman. Nonetheless, his love is not reciprocated, and he is also looking for lost love and wants to return to the way it used to be. In conclusion, the use of figurative language in song lyrics makes the song more interesting and has its meaning in adding messages contained in each figurative language itself.